PENGARUH PERMAINAN TRADISIONAL LARI BALOK TERHADAP PENINGKATAN KEMAMPUAN GERAK DASAR LOKOMOTOR SISWA KELAS V DI SD NEGERI 006 PALEMBANG - Gazelo Nagasondi, Jesly; Rizhardi, Rury; Nita, Perabu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic locomotor movement skills are fundamental abilities that elementary school students must possess because they support physical activities and motor development. However, preliminary observations at SD Negeri 006 Palembang indicated that students' locomotor skills were still not optimal, particularly in agility,balance, and speed. This study aimed to determine the effect of the traditional block-running game on improving the locomotor movement skills of fifth-grade students at SD Negeri 006 Palembang. This study employed a quantitative approach with a one-group pretest-posttest design. The sample consisted of 24 students from class V.B selected through purposive sampling. Research instruments included the 4 x10 meter Shuttle Run test to measure agility, the Stork Stand Positional Balance test to measure balance, and the 30-meter sprint test to measure speed. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, and paired sample tests with SPSS version 27. The results showed that the average pretest score of 56.921 increased to 73.558 in the posttest. The paired sample test showed a significance value of 0.001 < 0.05. Therefore, it can be concluded that the traditional block-running game significantly affects the improvement of locomotor movement skills among fifth-grade students at SD Negeri 006 Palembang. The traditional block-running game can be used as an effective alternative learning activity in physical education to improve students' locomotor movement skills.